Sufficiency and transformation–A semi-systematic literature review of notions of social change in different concepts of sufficiency - Lage, Jonas (Frontiers in Sustainability, 2022)
Sufficiency is an indispensable strategy for sustainable development that is gaining growing attention in both the scientific and the political sphere. Nevertheless, the question of how sufficiency-oriented social change can be shaped by different actors remains unclear. There are many different concepts of sufficiency and all of them entail certain notions of social change. However, these notions of social change remain mostly implicit. By conducting a semi-systematic literature review on sufficiency and transformation, this article makes explicit notions of social change in various concepts of sufficiency. Additionally, these notions are structured and discussed concerning their possible contribution to a broader socio-ecological transformation to advance the debate about sufficiency-oriented strategies. The literature was sampled by a systematic search in the databases of Web of Science and the ENOUGH-Network, a European network of sufficiency researchers, and complemented by texts known to the author. In total 133 articles, books and book chapters were reviewed. The sufficiency concepts were analysed regarding two dimensions: the goal of and the approach towards social change. Various ecological and sometimes social goals that different concepts of sufficiency pursue were identified. Some scholars operationalize the social and ecological goals in a sufficiency-specific way as consumption corridors or a pathway towards a post-growth economy. Furthermore, three different approaches to sufficiency-oriented social change were identified: a bottom-up-approach, a policy-making-approach and a social-movement-approach. Specific contributions and limitations of these approaches were identified. The three approaches differ regarding the role of conflicts and the conceptualisation of behaviour and social practices. By interpreting the results utilizing the Multi-Level-Perspective of Sustainability Transition Research and Erik O. Wright’s transformation theory, synergies for sufficiency-oriented social change were identified. The review founds a theoretical basis for further empirical and theoretical research on shaping sufficiency-oriented social change.